Digital photogrammetry for the 3D model of the archeological site of Todos Santos, Cuenca (Ecuador) - Aparicio Resco, Pablo; Espinoza-Figueroa, Freddy; Aguirre Ullauri, María del Cisne; Mejía Coronel, Paulina; Matovelle Jara, Cristian (Estoa. Journal of the Faculty of Architecture and Urbanism, 2018)
Advances in technology have changed the perspective of the human being on the world; in recent years there has been a rapid increase in technological advances in various fields, conservation and management of cultural heritage have not remained indifferent, three-dimensional digital photogrammetry has broken in its favor, especially in the field of documentation, with possibilities of being used for multiple purposes, involving patrimonial assets such as the case of the archaeological site of Todos Santos in Cuenca (Ecuador), characterized by evidence of three cultures: Cañari, Inca and Española. In this site, a photogrammetric survey was carried out framed in a formative experience that included the process of construction of the 3D model, from the taking of images, to the work in different softwares and the final renderings. The possibilities of this process are versatile, however, complementary as a technical input of knowledge and dissemination to traditional documentation techniques; for cases where its potential contributes to the integral conversation and is adjusted to the availability of existing resources.